54.3k views
0 votes
Which of the following equation has one solution?

Responses

4x + 2x = 6x - 4

3 (2x + 4) = 2 (2x - 4)

5(x - 3) = 5x - 3

2x = 2x + 4

1 Answer

0 votes

a) 4x + 2x = 6x - 4

= 6x = 6x - 4

cannot be solved further.

b) 3(2x + 4) = 2(2x - 4)

= 6x + 12 = 4x - 4

(bring the numbers and variables on one side)

= 6x + 4x = 12 - 4

10x = 8

x = 8/10 = 4/5

can be solved.

c) 5(x - 3) = 5x - 3

= 5x - 15 = 5x - 3

= (bring the variables and numbers on one side)

5x + 5x = -15 - 3

= 10x = -18

x = -18/10 = 9/5

can be solved

d) 2x = 2x + 4

= 2x + 2x = 4

= 4x = 4

x = 4/4 OR 1.

THUS, (B, (C AND (D CAN BE SOLVED WITH ONE SOLUTION.

User David Kay
by
4.8k points